PEMAHAMAN HADIS MELALUI KONTEN ANIMASI 'HAFIZ HAFIZAH': MEMBANGUN PENDIDIKAN ANAK YANG ISLAMI DI ERA DIGITAL - Mas Ayu Ainun Nisa’; Mohammad Kurjum (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
In the midst of rapid technological development, animation media has become one of the most effective educational tools for introducing Islamic values to children, including the study of hadith. Over time, hadiths have been presented through engaging media such as animated content. Given the importance of hadith as the second source of Islamic law after the Qur'an, accuracy and appropriateness in conveying hadiths through any medium, including animation, becomes a crucial issue. This study aims to analyze the conformity of the understanding of hadiths presented in the "Hafiz Hafizah" animation with the commentaries of hadith books (kitab syarah hadith), as well as examine the positive implications of this Islamic animated content in fostering Islamic education for children in the digital era. The study uses content analysis methods on five episodes of the "Hafiz Hafizah" animation that feature the understanding of hadiths. The findings show that the understanding of hadith conveyed through the "Hafiz Hafizah" animation aligns with explanations in hadith commentaries. Moreover, this Islamic animated content has several positive implications, including facilitating the dissemination of Islamic values through engaging media, enhancing children's understanding of the Qur'an and hadith, and strengthening the bond between parents and children in religious education.